2011
DOI: 10.1016/j.ijgo.2011.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal repair of complex and complicated vesicovaginal fistulae

Abstract: The transvaginal approach to the repair of complex and complicated VVF gives good long-term results with low complication rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
15
2
3
Order By: Relevance
“…13,14 The short duration of the fistula among patients in this study also explains why the rate of divorce and other disruption of the wellbeing of affected women were not prominent among patients in this study. 1,11,14 This study has demonstrated that the use of the described modified surgical repair technique for the closure of selected complex VVF among patients in this study had a significantly higher (p= 0.0004) success rate than the use of the conventional technique of repair. This study was born out of a desire to discover a surgical technique that could give a one-chance opportunity of cure in selected complex cases of vesicovaginal fistula.…”
Section: Discussionmentioning
confidence: 76%
“…13,14 The short duration of the fistula among patients in this study also explains why the rate of divorce and other disruption of the wellbeing of affected women were not prominent among patients in this study. 1,11,14 This study has demonstrated that the use of the described modified surgical repair technique for the closure of selected complex VVF among patients in this study had a significantly higher (p= 0.0004) success rate than the use of the conventional technique of repair. This study was born out of a desire to discover a surgical technique that could give a one-chance opportunity of cure in selected complex cases of vesicovaginal fistula.…”
Section: Discussionmentioning
confidence: 76%
“…There have been several published studies favoring the transvaginal approach for both obstetric and gynecologic fistulae. [12][13][14][15] Although there are a limited number of patients in our study, mean operative time is 70 minutes, mean hospital stay is less than 24 hours, and the operations were completed with minimal bleeding. In addition, none of our patients needed additional analgesics other than nonsteroidal anti-inflammatory agents.…”
Section: Discussionmentioning
confidence: 92%
“…1,11,12 The relative advantages of a transvaginal approach are shorter operative time and hospital stay, minimal blood loss and postoperative pain, absence of the need for opening the bladder, possibility of performing anti-incontinence procedures, and availability of local interpositional flaps, when compared with an abdominal approach. 1,12 In addition, the transvaginal approach offers direct access to the fistula without entering the abdomen and is less invasive. There have been several published studies favoring the transvaginal approach for both obstetric and gynecologic fistulae.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly the surgical causes were mainly due to hysterectomies. 11 Thirdly, a general miscellaneous group which include causes like radiation for malignancy, foreign bodies and inflammatory diseases. 12 In all of our patients repaired by transabdominal approach we interposed omentum between the vagina and urinary bladder.…”
Section: Discussionmentioning
confidence: 99%